Prediction of Blood Pressure by Waist Circumference, Waist Pelvic Ratio and Body Mass Index - Wrahathinggih, Angesti Widipinasti; Wisnu, Nurwening Tyas; Sumasto, Hery (Humanistic Network for Science and Technology (HNST), 2018)
Hypertension cases in Yogyakarta are above the average cases of hypertension Indonesia. Hypertension can be prevented by controlling weight. Obesity indicators include; waist circumference, waist circumference ratio and Body Mass Index (BMI). The objectives of the study were to predict blood pressure based on the size of the waist circumference, waist lumbar ratio and body mass index (BMI). The cross-sectional study method. Samples of GKJ Gondokusuman Yogyakarta congregation, male and female, age 20-39 and 40-59 years old. Sampling proportionate stratified random sampling. Data analysis with Pearson test. The result showed that there was a relationship of waist circumference with systolic blood pressure and diastole, there was a relationship between body mass index with systolic and diastolic blood pressure. In the female group, there was no relationship between waist circumference, waist lumbar ratio, and BMI with systolic or diastolic blood pressure. Keywords: Waist circumference, Waist lumbar ratio, BMI, Blood pressure, Obesity